2004
DOI: 10.3354/meps283055
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the chemical plume behind a sinking particle in a turbulent water column

Abstract: Many aquatic organisms, from bacteria to crustaceans, use chemical plumes released by sinking particulate organic material either directly as a food source or as a signal to find potential food items (marine snow aggregates, fecal pellets). This work examines how the relevant metrics of the plume (length, volume and cross sectional area) relate to encounter rates and how they vary with turbulence. Total plume length appears to be invariant to turbulent shear rate, although plume volume and cross section do dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…We have assumed, for example, that a chemical trail that is intercepted by a male is detected with a likelihood that is independent of the distance downstream the female, while in fact pheromone concentration and, thus, trail detectability declines with increasing distance (Bagøien and Kiørboe in press a). Moreover, in the ocean, turbulence may interfere with both chemical and hydromechanical signals (Visser 2001;Visser and Jackson 2004). In that sense, our calculations may be considered as estimates of potential search volumes.…”
Section: Discussionmentioning
confidence: 99%
“…We have assumed, for example, that a chemical trail that is intercepted by a male is detected with a likelihood that is independent of the distance downstream the female, while in fact pheromone concentration and, thus, trail detectability declines with increasing distance (Bagøien and Kiørboe in press a). Moreover, in the ocean, turbulence may interfere with both chemical and hydromechanical signals (Visser 2001;Visser and Jackson 2004). In that sense, our calculations may be considered as estimates of potential search volumes.…”
Section: Discussionmentioning
confidence: 99%
“…There is nothing to suggest that one strategy is better than the other in terms of enhancing mate encounter rates (Kiørboe & Bagøien 2005). However, chemical signals are susceptible to ambient fluid motion, and Visser & Jackson (2004) have described how chemical trails, like the pheromone trails described for copepods, are eroded by turbulence. Fluid shear stretches the trail, makes it thinner and therefore more susceptible to molecular diffusion, and eventually breaks up the trail into shorter filaments.…”
Section: Pheromone Clouds Vs Pheromone Trails: Susceptibility To Turmentioning
confidence: 99%
“…This is, however, not necessarily the case. Visser & Jackson (2004) showed that chemical trails are robust to turbulence as long as γL /u < 1, where γ is the along-trail shear rate, L the trail length and u the cruising velocity of the female. Because γ = (ε/6η) 1/2 , where ε is the turbulent dissipation rate and η fluid viscosity (~10 -2 cm 2 s -1 for seawater), it follows that one can define a critical dissipation rate, above which turbulent erosion of chemical trails become significant, as:…”
Section: Pheromone Clouds Vs Pheromone Trails: Susceptibility To Turmentioning
confidence: 99%
“…Thus, the diameter of the depletion region around each bacterium (1m) is small relative to the spacing between cells (Fig.2). (Visser and Jackson, 2004). The figure portrays the distribution of plume sizes that exist for a typical particle size distribution but is not meant to show the actual distribution to be expected.…”
Section: How Extensive Is Bacterial Depletion?mentioning
confidence: 99%
“…There are promising approaches to parameterizing the patchiness of larger plumes in the presence of turbulence (e.g. Visser and Jackson, 2004), but further work is needed if the approach developed here is to be extended to larger organisms and scales.…”
Section: -3mentioning
confidence: 99%